Kommos - An Excavation on the South Coast of Crete : The Kommos Region and Houses of the Minoan Town. Part I: the Kommos Region, Ecology, and Minoan Industries - Shaw, Joseph W. (Princeton Legacy Library, 2014)
Cover -- Contents.